From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Cerveau, sexe et idéologie - Vidal, Catherine (Diogène, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; discours dominant; europe; fem1000; france; neurobiologie; premier cycle; psy4910; périodes historiques; ressource en ligne; régions géographiques; sciences; stéréotypes; systèmes d'oppressions; thématiques

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie

Le sexe prescrit : la différence sexuelle en question - Prokhoris, Sabine (Aubier, 2000)
La psychanalyse serait-elle la gardienne de la «loi symbolique» ? Nombre de discours veulent nous en persuader. Car c’est la «différence des sexes», dont la psychanalyse est supposée détenir la raison, qui serait l’alpha et l’oméga de notre humanité. Homme ou femme, il faudra donc qu’on se le tienne pour dit, et qu’on ne méconnaisse pas la «vérité» de l’ordre sexuel. Cet ordre pourtant est-il autre chose que l’effet, normatif, de certaines relations de pouvoir que l’on se garde bien d’interroger ? Effet très concret car il traverse la trame de chaque existence, en même temps qu’il sert de socle à la figure de la famille à laquelle notre organisation politique donne droit – et devoir – de cité. Le psychanalyste est en prise directe sur cet enjeu. Car, dans la perspective inaugurée par Freud et marquée par Lacan, il traite la souffrance psychique en sa relation avec l’inconscient. Or l’inconscient, «discours de l’autre», prescrit ce que nous sommes, et d’abord quand il s’agit de la sexuation. Mais cette prescription est à entendre au double sens du terme : injonction et décret d’oubli. Quelle sera, face à cela, la politique de la psychanalyse ?
Keywords: cours; cycles supérieurs; discipline; europe; fem1000; fem7000; france; lit3220; politique; premier cycle; psychanalyse; régions géographiques; sciences; sciences humaines; sexualité; thématiques